Designing Augmented Reality-Based Learning Media for Facilitating Early Childhood's Naturalistic Intelligence - Rahman, Firda Nafaatur Rahman; Rahman, Taopik; Mulyana, Edi Hendri (Fakultas Tarbiyah dan Ilmu Keguruan UIN Sultan Aji Muhammad Idris Samarinda, 2024)
In facilitating naturalist intelligence, teachers often have difficulty presenting real objects in the classroom. Referring to the function of media in learning to overcome sensory limitations, space limitations and time limitations, media representations can illustrate abstract information so that it is clearer and more concrete. One of them is by using augmented reality-based media to present a 3D object in a real environment in real time. This study aims to develop learning media based on augmented reality to facilitate early childhood naturalist intelligence. The study used the EDR (Educational Design Research) method with research procedures adapted from the McKenney and Reeves model. Data analysis was performed using qualitative and quantitative analysis techniques. The findings from this study indicate that the developed augmented reality media meets the criteria with an eligibility percentage of 88,5 % for the material validator and 98% for the media validator. Based on these results, it can be concluded that this media is very feasible to be used as a means to facilitate the development of naturalist intelligence in early childhood